The effect of a multidisciplinary obstetric emergency team training program, the In Time course, on diagnosis to delivery interval following umbilical cord prolapse – A retrospective cohort study. (7th September 2016) - Copson, Sean; Calvert, Katrina; Raman, Puvaneswary; Nathan, Elizabeth; Epee, Mathias
Abstract : Background: Cord prolapse is an uncommon obstetric emergency, with potentially fatal consequences for the baby if prompt action is not taken. Simulation training provides a means by which uncommon emergencies can be practised, with the aim of improving teamwork and clinical outcomes. Aims: This study aimed to determine if the introduction of a simulation‐based training course was associated with an improvement in the management of cord prolapse, in particular the diagnosis to delivery interval. We also aimed to investigate if an improvement in perinatal outcomes could be demonstrated. Materials and methods: A retrospective cohort study was performed. All cases of cord prolapse in the designated time period were identified and reviewed and a comparison of outcome measures pre‐ and post‐training was undertaken. Results: Thirty‐one cases were identified in the pre‐training period, and compared to 64 cases post‐training. Documentation improved significantly post‐training. There were non‐significant improvements in use of spinal anaesthetic, and in the length of stay in the special care neonatal unit. There was a significant increase in the number of babies with Apgar scores less than seven at 5 min. There were no differences in the diagnosis to delivery interval, or in perinatal mortality rates. Conclusion: Obstetric emergency training was associated with improved teamwork, as evidenced by the improved documentation post‐training in this study, but not with improved diagnosis to delivery interval. Long‐term follow‐up studies are required to ascertain whether training has an impact on longer‐term paediatric outcomes, such as cerebral palsy rates.